The Dark Side of Overuse of Internet: A study of Indian college students - Binod Kumar Rajak; Sumanjeet Singh; Minakshi Paliwal (ACHSM, 2022)
Introduction: The extensive use of the internet and its effect on our lives can no longer be overlooked. While the internet is a result of the rapid advancement of science and technology, its impact on students depends on how they use it. The present study identifies Internet usage patterns, nature of use, and Internet Addiction (IA) among India's undergraduate and postgraduate students and its consequences on their lives. Methods: This empirical examination uses the Multistage Sampling Method (MSM) and cross-sectional method. The structured questionnaire distributed (N=1,200) to ungraduated college students. We included at least ten institutes of every state in India and thirty participants from each institution in this study. Results: The study revealed that overuse of the internet is statistically significant with internet addiction concerning gender but not with age and education. Overuse of the internet strongly impacts IA. The study further investigates the relationship with the consequences of overuse of the internet with age, gender and education and found that genders significantly differ with the physical and psychological problem but not with a behavioural and relationship problem; level of education has a significant difference with physical and behavioural problem but not with relationship and psychological problems. Conclusion: Our investigation helps college, university or educational policymakers to frame good mental health policies or create programmes to reduce or constrain the adverse effect of overuse of the internet. The results show a compelling need to reduce the overuse of the internet (OI) by promoting psychological competence.